PhET INTERACTIVE SIMULATION AS A VIRTUAL LABORATORY FOR SCIENCE LEARNING IN ELEMENTARY SCHOOL DURING THE COVID-19 PANDEMIC - Anna Roosyanti (Auladuna: Jurnal Pendidikan Dasar Islam, 2022)
Abstract This research aims to analyze the effectiveness of using PhET Interactive Simulation as a virtual laboratory for science learning in elementary schools during the Covid-19 pandemic. This research used a qualitative descriptive method. Data collection techniques used were literature review, questionnaire, and interview. Data analysis used was analysis techniques by Miles and Huberman. Based on the data analysis results, PhET Interactive Simulation was effectively applied to learn Science in Elementary School during the Covid-19 pandemic. Students could find the science concepts by themselves with the help of PhET Interactive Simulation to make learning more meaningful. PhET Interactive Simulation was proven able to visualize concepts that were initially difficult to understand. Based on the research results, it can be concluded that PhET Interactive Simulation was effectively applied as a virtual laboratory in Elementary schools during the Covid-19 pandemic. In its application, it is better to provide a user guide in the form of audiovisual or video.